USING THE INFORMATION RESOURCE CENTER TO CREATE INDEPENDENT EDUCATIONAL ASSIGNMENTS - Khursanov, Nurislom (MMIT Proceedings, 2023)
The higher education system in the world is important because it is based on the independent activity of students. In the scientific literature on language teaching in developed countries, special attention is paid to the content and effectiveness of independent educational tasks and independent educational tasks, and in the educational process, questions, rapid question-and-answer game technologies, task and text analyzes and exercises are effectively used from independent educational tasks. In the international experience, the educational tasks focus on effective communication. The independent learning assignments used in practice are developed based on certain criteria established in advance.